PENGARUH PEMBERDAYAAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KABUPATEN MERAUKE - Aldisa Arifudin; Nursin Brasit; Dian Parawansa (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Human resources is the most important asset owned by an organization because of its role as executor of policies and operational activities in achieving organizational goals. This study aims to determine to determine the effect of Organizational Empowerment and Culture against Job Satisfaction and Employee Performance of the Office of Transportation of Merauke Regency. This research uses quantitative method. This type of research is descriptive research is causal (causal), to determine the effect of a variable on other variables. In this study using path analysis model (path analysis) because among independent variables with dependent variable there is mediation that influence. This analysis is assisted with the help of SPSS 20.0 software. The result of test that have been done show that empowerment have positive and significant effect to job satisfaction, organizational culture have positive and significant effect to job satisfaction, empowerment have negative and insignificant effect to employee performance, organizational culture have positive and significant effect to employee performance, job satisfaction have positive effect and significant to employee performance, job satisfaction mediate the influence of empowerment to employee performance, job satisfaction mediate influence between organizational culture on employee performance.